Seroprevalence of SARS-CoV-2 antibodies in healthcare workers at a London NHS Trust. (4th February 2021) - Grant, Joseph J.; Wilmore, Stephanie M.S.; McCann, Naina S.; Donnelly, Owain; Lai, Rebecca W.L.; Kinsella, Matthew J.; Rochford, Helena L.; Patel, Trupti; Kelsey, Michael C.; Andrews, Julie A.
Abstract: Healthcare workers (HCWs) have a theoretically increased risk of contracting severe acute respiratory coronavirus virus 2 (SARS-CoV-2) given their occupational exposure. We tested 2, 167 HCWs in a London Acute Integrated Care Organisation for antibodies to SARS-CoV-2 in May and June 2020 to evaluate seroprevalence. We found a seropositivity rate of 31.6% among HCWs.